2020
DOI: 10.4103/jpbs.jpbs_175_19
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of medicinal plants: Basic extraction and fractionation procedures for experimental purposes

Abstract: Preparation of medicinal plants for experimental purposes is an initial step and key in achieving quality research outcome. It involves extraction and determination of quality and quantity of bioactive constituents before proceeding with the intended biological testing. The primary objective of this study was to evaluate various methods used in the preparation and screening of medicinal plants in our daily research. Although the extracts, bioactive fractions, or compounds obtained from medicinal plants are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
488
1
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(526 citation statements)
references
References 8 publications
13
488
1
24
Order By: Relevance
“…Maceration with continuous stir is another common approach to obtain antibacterial compounds from microalgae. It is inexpensive and easy to perform, and it allows the extraction of non-heat stable compounds, but it has the disadvantages of requiring long extraction time, and filtration or centrifugation followed by evaporation of solvent after extraction (Abubakar and Haque 2020). In sonication, or ultrasound-assisted extraction, high frequency energy (higher than 20 kHz) is applied to microalgal cells allowing solvent penetration (Abubakar and Haque 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Maceration with continuous stir is another common approach to obtain antibacterial compounds from microalgae. It is inexpensive and easy to perform, and it allows the extraction of non-heat stable compounds, but it has the disadvantages of requiring long extraction time, and filtration or centrifugation followed by evaporation of solvent after extraction (Abubakar and Haque 2020). In sonication, or ultrasound-assisted extraction, high frequency energy (higher than 20 kHz) is applied to microalgal cells allowing solvent penetration (Abubakar and Haque 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Water has the highest polarity of 1,000 followed by methanol (0.762) and finally, ethanol (0.654). The compounds extracted by these highly polar solvents differ in quantity and quality (Abubakar and Haque, 2020). Many studies have demonstrated the effect of the solvent type on the inhibitory potential of plant extracts (Aljuraifani 2017; Ababutain 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In general, extraction procedures incorporated were maceration and Soxhlet extraction. The choice of an appropriate extraction method normally depends on the nature of the plant material, solvent used, pH of the solvent, temperature, and solvent to sample ratio [10]. Water is the most polar solvent and is used in the extraction of a wide range of polar compounds and it dissolves a wide range of substances, alcohol could extract polar secondary metabolites while ether is a nonpolar solvent and is useful in the extraction of compounds such as alkaloids, terpenoids, and fatty acids [11,12].…”
Section: Discussionmentioning
confidence: 99%